Electroluminescence from a n-ZnO nanorod/p-CuAlO2 heterojunction light-emitting diode - Qi, K. C. (2012)
n-ZnO nanorod/p-CuAlO2 heterojunction light-emitting diodes have been fabricated on p+-Si substrates. The CuAlO2 thin film was deposited by dc-magnetron sputtering while the ZnO nanorods (NRs) were fabricated using the vapor-phase transport method. The current–voltage characteristics of the devices showed good rectifying behavior with a high forward-to-reverse current ratio of around 120 at ±7V. Strong ultraviolet electro-luminescence centered at ~390 nm and a broad green-band emission were observed from the diode at room-temperature. The p-CuAlO2 layer was found to facilitate hole injection from p+-Si into n-ZnO while confining the electrons at ZnO/CuAlO2 interface, thus effectively enhancing the recombination emission efficiency in ZnO NRs.